العلاقة بين نطق الأصوات العربية والتعبير الشفهي في المدرسة محمدية المتوسطة 6 داوو مالانج - Niswah, Luthfiyyatin; Hasanah, Mamluatul (Program Studi Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
ملخص نطق الأصوات العربية له دور مهم في مهارة الكلام. مع نطق واضح وطلاقة لكل صوت حرف، يكون الشخص قادرا على فهم ما يقوله للمحاور. إذا تم نطق الأصوات العربية، فستكون مهارة الكلام مثالية وستعمل عملية الاتصال بسلاسة. انطلاقا من هذه الفرضية، يهدف هذا البحث إلى معرفة: 1) نطق الأصوات العربية لدى الطلبة، 2) التعبير الشفهي لدي الطلبة، 3) العلاقة بين نطق الأصوات العربية والتعبير الشفهي لدي الطلبة. منهج البحث المستخدم هو منهج كمي بنوع دراسة العلاقة. أجري البحث في مدرسة المحمدية المتوسطة ٦ داوو مالانج للعام الدراسي 2022-2023. كانت تقنية جمع البيانات المستخدمة عبارة عن اختبار شفهي كأداة لقياس نطق الأصوات العربية والتعبير الشفهي للطلبة وتم تحليلها باستخدام التحليل الإحصائي الوصفي وتحليل ارتباط بيرسون ثنائي المتغير مع SPSS الإصدار ٢٥. أظهرت النتائج أن: 1) بلغ توسط طلبة في نطق الأصوات العربية الى 3.20. بلغ نسبة ٥١% من الطلبة يدخلون في فئة كفاءة عالية، و٤١% يحصلون على فئة كفاءة متوسطة، و٧% منهم يدخلون في فئة كفاءة مقبولة. 2) بلغ توسط طلبة في التعبير الشفهي الى 2.98. مما يصل إلى ٣٨% من الطلبة في فئة التقييم كفاءة عالية و ٤٧% منهم في فئة كفاءة متوسطة، و ١٤% من الطلاب في فئة كفاءة مقبولة. 3) أظهرت نتائج اختبار الفرضية قيمة معامل ارتباط ٠.٧٦٢ بقيمة Sig.2 ذيل ٠.٠٠٠ أصغر من ٠.٠٥ ثم يتم قبول Ha ورفض Ho. بناء على تحليل اختبار الفرضية، تم التوصل إلى وجود علاقة قوية وموجبة بين نطق الأصوات العربية والتعبير الشفهي. الكلمات المفتاحية: نطق الأصوات العربية، التعبير الشفهي، مهارة الكلام ABSTRACT Ashwat arabiyyah pronunciation plays an important role in speaking skills. With clear and eloquent pronunciation of each letter sound, a person is able to understand what he is saying to his interlocutor. If ashwat arabiyyah has been mastered, speaking skills will be perfect and the communication process will run smoothly. Starting from this hypothesis, this study aims to determine: 1) students' pronunciation of ashwat arabiyyah, 2) students' oral expressions, 3) the relationship between ashwat arabiyyah's pronunciation and oral expressions. The research method used is a quantitative approach to the type of correlation research. The research was conducted at SMP Muhammadiyah 06 Dau Malang for the academic year 2022-2023. The data collection technique used was an oral test as a tool to measure the pronunciation of ashwat arabiyyah and students' oral expressions and analyzed using descriptive statistical analysis and pearson bivariate correlation analysis with SPSS version 25. The results showed that: 1) the average students' ashwat arabiyyah pronunciation was 3.20. With a percentage of 51% of students included in the very competent assessment category, 41% obtained competent criteria, and 7% of students were included in the fairly competent category. 2) the average of students' oral expression reached 2.98. As many as 38% of students fall into the very competent category, 47% of students fall into the competent category, and 14% of students fall into the criteria of quite competent. 3) the results of the hypothesis test show a correlation coefficient value of 0.762 with a tailed sig.2 value of 0.000 which is smaller than 0.05, so Ha accepted and HOrejected. Based on the analysis of hypothesis testing, it can be concluded that there is a strong and positive relationship between the pronunciation of ashwat arabiyyah and oral expression. Keywords: Ashwat Arabiyyah Pronunciation, Oral Expression, Maharah Kalam